SARS-CoV-2 Spike Protein 1 Activates Microvascular Endothelial Cells and Complement System Leading to Platelet Aggregation - Perico, Luca; Morigi, Marina; Galbusera, Miriam; Pezzotta, Anna; Gastoldi, Sara; Imberti, Barbara; Perna, Annalisa; Ruggenenti, Piero; Donadelli, Roberta; Benigni, Ariela; Remuzzi, Giuseppe (Frontiers in Immunology, 2022)
Microvascular thrombosis is associated with multiorgan failure and mortality in coronavirus disease 2019 (COVID-19). Although thrombotic complications may be ascribed to the ability of SARS-CoV-2 to infect and replicate in endothelial cells, it has been poorly investigated whether, in the complexity of viral infection in the human host, specific viral elements alone can induce endothelial damage. We performed an ELISA to detect circulating spike protein in the sera of severe COVID-19 patients. In vitro experiments were performed on human microvascular endothelial cells from the derma and lung exposed to SARS-CoV-2-derived spike protein 1 (S1). The expression of adhesive molecules was studied by immunofluorescence and leukocyte adhesion and platelet aggregation were assessed under flow conditions. Western Blot analysis was used to investigate angiotensin converting enzyme 2 (ACE2) and AMPK expression. In addition, S1-treated endothelial cells were incubated with anti-ACE2 blocking antibody, AMPK agonist, or complement inhibitors. We showed that significant levels of spike protein were found in the 30.4% of severe COVID-19 patients. In vitro, the activation of endothelial cells with S1 protein, via ACE2, impaired AMPK signalling, leading to robust leukocyte recruitment due to increased adhesive molecule expression and thrombomodulin loss. This S1-induced pro-inflammatory phenotype led to exuberant C3 and C5b-9 deposition on endothelial cells, along with C3a and C5a generation that further amplified S1-induced complement activation. Functional blockade of ACE2 or complement inhibition halted S1-induced platelet aggregates by limiting von Willebrand factor and P-selectin exocytosis and expression on endothelial cells. Overall, we demonstrate that SARS-CoV-2-derived S1 is sufficient in itself to propagate inflammatory and thrombogenic processes in the microvasculature, amplified by the complement system, recapitulating the thromboembolic complications of COVID-19.